The fish can rot from the heart, not just the head: Exploring the detrimental impact of transgressions by leaders at multiple levels of an organization - Maskor, Mazlan; Fladerer, Martin P.; Fong, Polly; Steffens, Niklas K.; Haslam, S. Alexander (British journal of social psychology, 2023)
In this registered report, we examined the effect of transgressions committed by leaders working at different group levels within an organization on employee outcomes. Based on social identity theorizing, we argued that organizational leader transgressions would affect organizational members’ experiences only at the organizational level, but that workgroup leader transgressions would impact organizational members’ experiences at both workgroup and organizational levels. To test these ideas, we developed a 2 (leader group affiliation: workgroup vs. organizational) × 2 (leader behaviour: normative vs. transgressive) between‐subjects experimental paradigm. As hypothesized, both workgroup and organizational leader transgressions resulted in decreased organizational identification and perceived organizational leader effectiveness. Contrary to our prediction, transgressions of both workgroup and organizational leaders were similarly detrimental to workers’ workgroup identification. However, as predicted, a transgressive workgroup leader had a greater negative impact on perceived workgroup leader effectiveness than a transgressive organizational leader. When outliers were excluded, a workgroup leader’s transgression was found to be more detrimental to work performance than an organizational leader’s transgression. Overall, this study demonstrates that the transgressions of lower‐level workgroup leaders can be as detrimental – and in some cases more detrimental – to workers than the transgressions of higher‐level organizational leaders.